(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The main practice of the ancient Mediterranean religion was the sacrifice of animals, including the slaughter and the gifting of one or more animals. Traditional blood offerings were part of a life and death cycle that should thrive both animals and humans. Throughout the Empire Christians and pagans alike rejected such sacrifices. This article discusses the pagan and Christian critiques of Greco-Roman blood sacrifices. Authority was founded on the cultural killing of animals and the distribution and eating of their flesh in an old sacrificial discourse. In the new soteriological discourse, power was founded on a symbolic capital of moral and physical pureness and intellectual insights, and the goals of spiritual perfection and redemption. Some of the religions that participated in the new conversation, although Christianity banned it, continued to practice animal sacrifice. Direct human body screening for medicine and future study, as well as electronic medical data, are both useful in minimizing biomedical research sacrifice for animals. These techniques and strategies of research may be more economical and applied to a range of human health issues.